Keanekaragaman spesies parasitoid telur Helicoverpa armigera (Hübner) pada sistem tanam monokultur dan polikultur kapas - nurindah nurindah; Sujak Sujak (Perhimpunan Entomologi Indonesia, 2006)
Polyculture system is one of techniques in pest management. In Indonesia, cotton is always intercropped with second food crops such as maize, soybean, mungbean or peanut. This research was aimed to evaluate the effect of culture system, i.e. cotton monoculture vs. cotton intercropped with soybean on the increase of species diversity of H. armigera egg parasitoids and the parasitoid contribution to mortality of H. armigera. The research was arranged in a split plot design with two main factors: three cotton varieties with three levels of trichome density (Tamcot SP 37, Kanesia 8 and LRA 5166) and the subplots were two cultivation systems (cotton monoculture and polyculture), with three replicates. Observations were made by collecting H. armigera eggs on population of first generation (45 days after planting) and second generation (75 DAP). The results showed that on cotton polyculture the egg parasitoid complex which consisted of Trichogramma spp. and Trichogrammatoidea spp. was higher than that in cotton monoculture and so was the egg parasitism level. The increase of egg parasitism was 24% in the first generation and 15% in the second generation. Parasitoid species found belonged to the genera Trichogramma and Trichogrammatoidea. In the parasitoid complex, Trichogrammatoidea armigera was dominant on the first generation and Trichogramma chilotraeae on the second. The domination succession could be as a result of the higher host-searching capacity of T. chilotraeae than that of T. armigera.